2017
DOI: 10.5723/kjcs.2017.38.3.33
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Among Sleep Problems, Executive Function and Social Behavior During the Preschool Period

Abstract: This study examined the relationships among sleep problems, executive function and social behavior during the preschool period. In addition, the mediating role of executive function between sleep problems and social behavior was investigated. Methods: A total of 304 preschool children participated in this study. The data were collected through maternal reports. Results: First, preschoolers' sleep problems were found to be significantly related to overt aggression and prosocial behavior. Second, preschoolers wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 66 publications
1
7
0
3
Order By: Relevance
“…The results of this study provide evidence of the reciprocal associations between executive dysfunction and happiness in a sample of Korean children. Our findings are consistent with prior research on the effects of EF on socio-emotional functions [10,13,16,17] and behavioral problems [3,9,14,15]. In addition, the results are consistent with the literature on the effects of emotion on EF [20,26], particularly positive emotions [14,30,32].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of this study provide evidence of the reciprocal associations between executive dysfunction and happiness in a sample of Korean children. Our findings are consistent with prior research on the effects of EF on socio-emotional functions [10,13,16,17] and behavioral problems [3,9,14,15]. In addition, the results are consistent with the literature on the effects of emotion on EF [20,26], particularly positive emotions [14,30,32].…”
Section: Discussionsupporting
confidence: 92%
“…For instance, Park et al found that parent ratings of children's EF difficulties in second grade predicted problem behaviors in third grade [14]. Shin and her colleagues also showed that parent ratings of preschoolers' executive dysfunction was positively associated with depressive symptoms and aggressive behaviors [15].…”
Section: Introductionmentioning
confidence: 99%
“…6-11 3 (Rohlf, Holl, Kirsch, Krahé, & Elsner, 2018), 1-2 2 (Riggs, Blair, & Greenberg, 2003), 1 4 , 5 6 (Jacobson, Williford, & Pianta, 2011). , Kim & Oh, 2014), (Shin, Park, Kim, Yun, & Yoon, 2017) , (Hwang & Song, 2013;Lam et al, 2018;Y.-J. Lee et al, 2014;Lucassen et al, 2015;Towe-Goodman et al, 2014).…”
mentioning
confidence: 99%
“…, Choi & Song, 2013) , (Carlson & Wang, 2007) . (Kong & Lim, 2012a, 2012bN. Shin et al, 2017), (Kong & Lim, 2012a, 2012bN.…”
Section: 매개효과 분석mentioning
confidence: 99%
“…, (Waters & Sroufe, 1983) . (Kong & Lim, 2012a, 2012bN. Shin, Park, Kim, Yun, & Yoon, 2017), (N. Shin et al, 2017;Sulik et al, 2015), (B. Y.…”
mentioning
confidence: 99%